A Rare Cause of Endocarditis: Streptococcus pyogenes - Bahadır Gültekin; Bahar Pirat; Özlem Kurt Azap; Ayşegül Yeşilkaya; Hande Arslan (Balkan Medical Journal, 2012)
Although group A β-hemolytic streptococcus is an uncommon cause of infective endocarditis, an increase in the incidence of invasive group A streptococcus infections including bacteremia has been reported in the last two decades. Herein we report Streptococcus pyogenes endocarditis in a previously healthy adult patient who was hospitalized to investigate the etiology of fever. Because of a suspicion of a new vegetation appeared in the second (aortic) valve in the 14th day of high dose penicillin G treatment, the mitral and aortic valves were replaced by mechanical prosthesis on the 22nd day of treatment. He was discharged from hospital after the 6 week course of antibiotic treatment.